2014
DOI: 10.1245/s10434-014-3749-8
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda III Thyroid Nodules: The Role of Ultrasound in Clinical Decision Making

Abstract: HA, IM, and MC were predictors of malignancy in Bethesda III nodules. In addition, the negative predictive value for any of these three criteria was high; a nodule that lacks all of these three criteria is thus unlikely to be malignant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
7
2
Order By: Relevance
“…Conversely, in one study including only nodules with Bethesda III cytology, echogenicity showed the highest IRR among other 5 individual features, with k value of 0.94. Notably all other features had moderate to substantial agreement as well [26]. Along with the results of our study, it could be suggested that this disparity is explained by the fact that nodules with Bethesda III cytology are a subset with more homogenous US characteristics.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Conversely, in one study including only nodules with Bethesda III cytology, echogenicity showed the highest IRR among other 5 individual features, with k value of 0.94. Notably all other features had moderate to substantial agreement as well [26]. Along with the results of our study, it could be suggested that this disparity is explained by the fact that nodules with Bethesda III cytology are a subset with more homogenous US characteristics.…”
Section: Discussionsupporting
confidence: 71%
“…In our study, the IRR for echogenicity was substantial with kappa value of 0.71. In previous cohorts of no specific subsets of thyroid nodules, echogenicity was consistently among the features with lower IRR (0.33-0.57) showing only fair to moderate agreement [3,[18][19][20][21][22][23][24][25][26]. Conversely, in one study including only nodules with Bethesda III cytology, echogenicity showed the highest IRR among other 5 individual features, with k value of 0.94.…”
Section: Discussionmentioning
confidence: 84%
“…In the original report of the BSRTC, the risk of malignancy has been reported as 5-15%, 15-30%, and 60-75% for Bethesda III, IV, and V, respectively [4]. In literature, the overall malignancy rates varied from 9.3% to 48.9% for Bethesda III [2,6,9,[17][18][19][20]. Several authors proposed subcategorization or subgroupings based on the cytological findings of FNAB [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…In the differential diagnosis of malignant thyroid nodules, various clinical and imaging methods can be used. Several ultrasonographic features such as microcalcifications, hypoechogenicity, irregularity, and being taller than wide can predict thyroid malignancy [ 6 , 7 ]. However, their use for predicting malignancy in indeterminate nodules is still questionable due to low specificity and accuracy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nodulectomy would not be considered in patients with either a family history of thyroid cancer or a history of previous head and neck irradiation. Recently, our unit has also demonstrated that a lack of hypoechogenic attenuation, irregular margins or microcalcifications on ultrasound has a high negative predictive value in excluding malignancy in Bethesda 3 nodules, making nodulectomy an attractive option in these cases . Clearly, there remains concern about the potential for complications, especially if the surgical procedure were to be undertaken by a less experienced surgeon.…”
Section: Discussionmentioning
confidence: 99%